2022
DOI: 10.1002/aenm.202200614
|View full text |Cite
|
Sign up to set email alerts
|

Learning From Plants: Lycopene Additive Passivation toward Efficient and “Fresh” Perovskite Solar Cells with Oxygen and Ultraviolet Resistance

Abstract: serious concern compared with other commercial solar cells. Moreover, experiments show that PSCs degrade quickly on timescales of minutes when exposed to both light and oxygen. In other words, the decomposition is extremely aggravated under both O 2 atmosphere and light illumination, [3] which becomes an urgent and necessary issue to be solved for employing the PSCs in practical conditions. Misra demonstrated that oxygen prefers to adhere to the perovskite surface by Van der Waals force [4] and causes electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 62 publications
1
75
0
Order By: Relevance
“…22.77 76.9 20.25 2019 [37] Betulin 1.106 23.43 81.57 21.15 2020 [36] Artemisinin 1.13 22.41 80.2 20.42 2020 [91] Capsaicin 1.13 23.10 83.81 21.88 2021 [45] Carnitine 1.12 21.70 82.78 20.12 2021 [92] Lycopene 1.10 23.47 76 19.63 2021 [93] Silk fibroin 1.102 23.85 75 19.6 2022 [94] Zinc oxalate 1.18 15.5 76.7 14.1 2022 [95] Lycopene 1.21 24.10 81.00 23.62 2022 [96] VC and VD2 the devices at the maximum power point (MPP) to explore their steady-state output performance to better understand the devices operating state, as shown in Figure 4e. Under continuous MPP tracking for 200 s, the steady-state efficiency of D4 maintained 94.7% of the original efficiency, while the PCE of D1 only retained about 87.3% of the original PCE, indicating that D4 has better PCE output stability.…”
Section: Oc [V]mentioning
confidence: 99%
“…22.77 76.9 20.25 2019 [37] Betulin 1.106 23.43 81.57 21.15 2020 [36] Artemisinin 1.13 22.41 80.2 20.42 2020 [91] Capsaicin 1.13 23.10 83.81 21.88 2021 [45] Carnitine 1.12 21.70 82.78 20.12 2021 [92] Lycopene 1.10 23.47 76 19.63 2021 [93] Silk fibroin 1.102 23.85 75 19.6 2022 [94] Zinc oxalate 1.18 15.5 76.7 14.1 2022 [95] Lycopene 1.21 24.10 81.00 23.62 2022 [96] VC and VD2 the devices at the maximum power point (MPP) to explore their steady-state output performance to better understand the devices operating state, as shown in Figure 4e. Under continuous MPP tracking for 200 s, the steady-state efficiency of D4 maintained 94.7% of the original efficiency, while the PCE of D1 only retained about 87.3% of the original PCE, indicating that D4 has better PCE output stability.…”
Section: Oc [V]mentioning
confidence: 99%
“…[39] Subsequently, Song et al further studied the oxygen and ultraviolet resistance of PSCs after lycopene passivation. [40] Ma et al have investigated that a Lewis base additive of nicotinamide can passivate surface and grain boundary defects to suppress nonradiative recombination, realizing grain growth and efficiency improvement. [33] Wang et al have reported that caffeine with two conjugated carbonyl groups has a strong interaction with Pb 2+ ions to deliver perovskite films with preferred orientation and excellent electronic properties, finally enhancing the thermal stability of the device.…”
Section: Introductionmentioning
confidence: 99%
“…[33] Wang et al have reported that caffeine with two conjugated carbonyl groups has a strong interaction with Pb 2+ ions to deliver perovskite films with preferred orientation and excellent electronic properties, finally enhancing the thermal stability of the device. [41] Subsequently, this group has systematically studied the effect of the constructive configurations of theophylline, [41] caffeine, [40] and theobromine on the surface-defect passivation of perovskite photovoltaics through theoretical analysis and experimental characterization. [42] It can be concluded that food-derived additives with widely available raw materials also act as a key factor in the preparation of low toxicity, high efficiency, and stable perovskite devices.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra of both samples exhibit sharp negative signals at around 453 nm. However, the bleach recovery of optimized PeNCs is slower than that of pristine PeNCs, indicating that PFTS could eliminate the trap states on PeNCs . Then the time-resolved PL decay spectra were performed to further illustrate the reason for improved optical properties, as shown in Figure d.…”
mentioning
confidence: 99%
“…However, the bleach recovery of optimized PeNCs is slower than that of pristine PeNCs, indicating that PFTS could eliminate the trap states on PeNCs. 30 Then the time-resolved PL decay spectra were performed to further illustrate the reason for improved optical properties, as shown in Figure 1d. The PL decay curves are fitted by a triexponential function and the PL decay parameters are listed in Table S1.…”
mentioning
confidence: 99%